Training and Assistance in Making Promotional Media IT-based at Batu Islamic High School: Pelatihan dan Pendampingan Pembuatan Media Promosi Berbasis IT di SMA Islam Batu - Alfiani AP. Rosyadi; Minatun Nadlifah; Arif H. Khusna (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2024)
This service activity aims to provide training and assistance at Batu Islamic High School in terms of helping promote the school using IT-based media. The activities carried out are divided into two things, namely training and assistance in optimizing school social media, and utilizing media for school promotion. Both activities were carried out by the service team and assisted by students so that they could run well. The flow of service carried out is socialization of activities, internal discussions of the service team, implementation of training, mentoring, and reflection on activities. This community service activity went well and produced output in the form of short videos made by teachers and students.